Media Multitasking and Performance of Executive Function Among Secondary-School Students in Indonesia - Wulandari, Astri; Hendrawan, Donny (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to examine the contribution of media multitasking in predicting the performance of executive function which covers inhibitory control, cognitive flexibility, and working memory among secondary-school students. This study used a quantitative approach with a cross-sectional study design. Research participants were secondary-school students aged 13 – 18 years who attended school in Jakarta, Bogor, Depok, Tangerang, and Bekasi areas (N = 192). Data were collected using convenience sampling. Media multitasking was measured through a media use questionnaire. EF components were calculated using a performance-based approach by employing the Go/No-Go Task for inhibitory control, the Dots-Triangle Task for cognitive flexibility, and the N-2-Back Task for working memory. All data were analyzed statistically by descriptive, assumption testing, and hierarchical regression analysis. The result shows that media multitasking only contributes significantly to predicting performance inhibitory control after controlling gender and age. However, media multitasking is not significantly associated with the performance of cognitive flexibility and working memory. This study found that the use of digital media is related to the ability of students to inhibit irrelevant stimuli in learning.